Electrochemical Stability and Reversibility of Aqueous Polysulfide Electrodes Cycled Beyond the Solubility Limit. Issue 6 (1st June 2022) - Pan, Menghsuan Sam; Su, Liang; Eiler, Stephanie L.; Jing, Linda W.; Badel, Andres F.; Li, Zheng; Brushett, Fikile R.; Chiang, Yet-Ming
Abstract : Batteries which use dissolved redox-active species, such as redox flow batteries (RFBs), are often considered to be constrained in their operation and energy density by the solubility limit of the redox species. Here, we show that soluble redox active electrolytes can be reversibly cycled deeply into the precipitation regime, permitting higher effective concentrations, energy densities, and lower costs. Using aqueous sodium polysulfide negative electrolytes cycled in the nominal Na2 S2 to Na2 S4 capacity range as an example, we show that the effective solubility can be increased from 5 M in the fully-dissolved state to as much as 10 M using the precipitation strategy. Stable cycling was observed at 8 M concentration over more than 1600h at room temperature. We also analyze the range of polysulfide electrochemical stability, and characterize the precipitate composition. This enhanced effective concentration approach may be generalized to other redox chemistries that utilize solubilized reactants, and may be especially useful for long-duration storage applications where slow charge-discharge rates allow equilibration of precipitated species with the redox-active solution.